Physico-Chemical and Functional Properties of Protein Concentrate from Lima Beans (Phaseolus lunatus) - Pham, Hoan; Nguyen, Vinh Tien; Trinh, Khanh Son (Journal of Technical Education Science, 2022)
The purpose of this study was to characterize physico-chemical properties (including chemical composition, molecular weight) and functional properties (including oil and water absorption capacities, emulsifying activity and emulsifying stability indexes, foaming ability, rheological properties) of protein concentrate from Lima beans (Phaseolus lunatus) (PPC). The PPC recovery and the protein yields were 11.56 and 67.66%, respectively. The PPC has the moisture, protein, fat, ash, and total carbohydrate contents of 9.50, 71.77, 0.22, 6.23, and 11.94%, respectively. This PPC has fractions with molecular weight ranging from 16 to 72 kDa which correspond to the 7S globulin (43 – 75 kDa) and 11S globulin (21 – 38 kDa) subunits and other polypeptides. Besides, the oil-absorption capacity of PPC (2.86 mL/g) was higher than that of soy protein isolate (2.29 mL/g), while their water-absorption capacity was insignificant different (p>0.05). Emulsification capacity, foamability of PPC increased with the increasing of its concentrations, its acidity or alkalinity. The obtained PPC can be used as an alternative to traditional sources of proteins for various applications in the food industry.